Distribution and Fate of Military Explosives and Propellants in Soil: A Review - John Pichtel (Applied and Environmental Soil Science)
Energetic materials comprise both explosives and propellants. When released to the biosphere, energetics are xenobiotic contaminants which pose toxic hazards to ecosystems, humans, and other biota. Soils worldwide are contaminated by energetic materials from manufacturing operations; military conflict; military training activities at firing and impact ranges; and open burning/open detonation (OB/OD) of obsolete munitions. Energetic materials undergo varying degrees of chemical and biochemical transformation depending on the compounds involved and environmental factors. This paper addresses the occurrence of energetic materials in soils including a discussion of their fates after contact with soil. Emphasis is placed on the explosives 2,4,6-trinitrotoluene (TNT), hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), and octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX), and the propellant ingredients nitroglycerin (NG), nitroguanidine (NQ), nitrocellulose (NC), 2,4-dinitrotoluene (2,4-DNT), and perchlorate.